TECHNOLOGIES FOR THE OBTAINING HIGHLY SOLUBLE POLYMER COMPOSITE MATERIALS WITH ACTIVE PHARMACEUTICAL INGREDIENTS - ЛІСОВИЙ, В. М.; ЛИЖНЮК, В. В.; КОСТЮК, В. Г.; ПАЩЕНКО, І. О.; СМІШКО, Р. О.; ГОЙ, А. М.; ПОВШЕДНА, І. О.; ІЩЕНКО , О. В.; ЯРЕМЕНКО, В. В.; БЕССАРАБОВ, В. І. (Technologies and Engineering, 2023)
Purpose. A review of literature sources on the main aspects of promising technologies for obtaining highly soluble solid dispersion systems, which can be effectively used to significantly increase the solubility of various active pharmaceutical ingredients (APIs). Methodology. Analytical review of scientific, chemical-technological, medical and pharmaceutical literature over the past 20 years. Findings. The main aspects of promising technologies for obtaining highly soluble polymer composite materials containing active pharmaceutical ingredients have been analyzed. It has been found that hot melt extrusion can be successfully used to increase the solubility of low melting point APIs, the solvent evaporation method is useful for increasing the solubility of high melting point APIs, and centrifugal fiber formation can increase the solubility of low melting point APIs without the use of solvents and with less risk material degradation compared to the melting method. Such a range of technologies for obtaining highly soluble forms of APIs allows you to choose a technique depending on the physicochemical characteristics of polymer carriers and APIs and at the same time achieve not only a significant increase in solubility, but also reduce the use of excessive doses and reduce the risks of side effects, as well as guarantee a quick potential effect. Originality. It is shown that the innovative technology of centrifugal fiber formation can become the basis for the development of polymeric solid dispersion systems for increasing the solubility of various active pharmaceutical ingredients. Practical value. The conducted studies prove that promising methods of forming solid dispersed systems and ensuring a high level of solubility of sparingly soluble APIs include well-predicted and accessible methods, such as solvent evaporation and hot melt extrusion, as well as innovative technology of centrifugal fiber formation. Such technologies may be promising for the creation of domestic medicinal products with controlled API release.